Factors associated with health-related quality of life in papillary thyroid microcarcinoma patients undergoing radiofrequency ablation: a cross-sectional prevalence study. (1st January 2020) - Lan, Yu; Jin, Zhuang; Zhang, Yan; Song, Qing; Xiao, Jing; Yan, Lin; Zhu, Yaqiong; Zhang, Mingbo; Luo, Yukun
Abstract: Purpose: To explore the association of demographic characteristics, clinical symptoms and the fear of the disease progression factors with the physical and mental summary components of the health-related of life (HRQoL) of the papillary thyroid microcarcinoma (PTMC) patients undergoing radiofrequency ablation (RFA). Methods: 123 PTMC survivors undergoing RFA were enrolled in this study from October 2019 to March 2020. Demographic, clinical symptoms and the fear of the disease progression data were collected. SF-36, THYCA-QoL and FoP-Q-SF were used to evaluate the HRQoL of patients, clinical symptoms and the fear of disease progression. A multivariate regression model was performed to evaluate the association between the independent variable and the HRQoL variable. Results: The average self-reported HRQoL score was 81.17 ± 15.48 for the PCS and 73.40 ± 18.03 for the MCS. The multivariate linear regression model shows that the factors related to a poorer PCS were dependent for the female patients, the symptoms of neuromuscular and the throat/mouth, the fear of disease progression; the psychological disorder, symptoms of throat/mouth, inability to concentrate were related to worse scores for the MCS. The condition that was most strongly related to a poorer HRQoL (in both PCS and MCS) was the fear of their physical health. Conclusions: The factors related to significantly worse HRQoL scores across PCS and MCS for PTMC survivors include the female gender, the symptoms of neuromuscular and the throat/mouth, the psychological disorder, inability to concentrate, and the fear of their own physical health. Identification, management, and prevention of these factors are critical to improving the HRQoL of patients.